Una crítica inmanente de la lógica de la relevancia - José M. Méndez (Crítica)
In this paper we propose a so-called "immanent críticism" of classical relevance logic R. We labeI this criticism "immanent" in the sense that Anderson and Belnap's syntactical and semantical intuitive concepts of relevance are not put under question. Instead, we examine the formal translations of these intuitive concepts and, in particular, the adequacy of system R to thern. We prove that Anderson and Belnap's concept of relevance is merely syntactic; further, we show that this concept is only a characterization, not a definition: relevance Jogic is essentially a relative matter. Finally, it is shown that system R is not adequate to this syntactical characterization and some other systems (adequate) are delineated. [J.M.]